Digital Teaching and Learning in Higher Education (transcript Verlag, 2023)
Digital collaboration has been established in higher education for many years. But when the Covid-19 pandemic struck, digital learning and virtual mobility became of utmost importance for higher education. In the international project »Digital and International Virtual Academic Cooperation« (DIVA), scholars from Israel, Australia, and Germany focused on intercultural learning and online collaboration. Based on their findings, they show how digital arrangements can be used in higher education, how digital teaching can be theorized, and what potential can be gained for post-pandemic teaching.